2022
DOI: 10.3390/ijms231911827
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Regression Analysis for the Adsorption of Remazol Dye by Romanian Brewery Waste By-Product, Saccharomyces cerevisiae

Abstract: Earth’s water balance and economy are becoming increasingly fragile due to overpopulation, global warming, severe environmental pollution and both surface and groundwater pollution. Therefore, it is essential to find solutions to the problems of water scarcity and water pollution. In this research, an experiment was designed to optimize the technique for the adsorption of Remazol Red F3B (RR) dye by lyophilized brewery yeast waste from the fermentation process. Moreover, we proved that brewery yeast is a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“… 31 The peaks at 1643, 1538, and 1241 cm −1 were observed as amide I, II, and III bands, respectively, which are the characteristic N–H vibrational peaks of yeast cell proteins. 32 The absorption peaks at 1064 cm −1 and 1391 cm −1 correspond to P O in –OPO 3 2− (phosphoryl) on the IBY surface and C O stretching of the protein carboxyl group, respectively. 33 The adsorption band of IBY-PA-CDP at –OH (3400 cm −1 ) was reduced compared to those of β-CD and IBY, suggesting that the –OH group of IBY or β-CD reacts with PA. 31 The adsorption band of IBY-PA-CDP at 1632 cm −1 was the overlapping peak of the hydroxyl group bending vibration of β-CD and the amide I band of IBY.…”
Section: Resultsmentioning
confidence: 99%
“… 31 The peaks at 1643, 1538, and 1241 cm −1 were observed as amide I, II, and III bands, respectively, which are the characteristic N–H vibrational peaks of yeast cell proteins. 32 The absorption peaks at 1064 cm −1 and 1391 cm −1 correspond to P O in –OPO 3 2− (phosphoryl) on the IBY surface and C O stretching of the protein carboxyl group, respectively. 33 The adsorption band of IBY-PA-CDP at –OH (3400 cm −1 ) was reduced compared to those of β-CD and IBY, suggesting that the –OH group of IBY or β-CD reacts with PA. 31 The adsorption band of IBY-PA-CDP at 1632 cm −1 was the overlapping peak of the hydroxyl group bending vibration of β-CD and the amide I band of IBY.…”
Section: Resultsmentioning
confidence: 99%
“…Although the theoretical adsorption capacities ( Q e.cat ) calculated from the model (904.1, 1356.3, and 1571.5 mg/g of LLB-MB for RhB; 988.3, 1415.9, and 1670.0 mg/g of LLB-MB@Fe 3 O 4 for RhB; 798.3, 1237.1, and 1570.1 mg/g of LLB-MB for TH; and 874.8, 1413.7, and 1680.4 mg/g of LLB-MB@Fe 3 O 4 for TH) were slightly lower than the experimental Q e (941.6, 1386.6, and 1606.5 mg/g of LLB-MB for RhB; 998.1, 1502.2, and 1698.2 mg/g of LLB-MB@Fe 3 O 4 for RhB; 831.4, 1298.0, and 1602.4 mg/g of LLB-MB for TH; and 896.1, 1453.5, and 1749.9 mg/g of LLB-MB@Fe 3 O 4 for TH), they still indicated that the PFK model may be applicable to the adsorption process in some aspects. At the same time, it also showed that the adsorption capacity will increase with the initial concentration increasing to some extent [ 42 , 43 ]. While Ho-McKay’s PSK model was used to fit the data, the correlation coefficients ( R 2 ) of LLB-MB and LLB-MB@Fe 3 O 4 ranged from 0.9987 to 0.9998 and from 0.9964 to 0.9998 for RhB and ranged from 0.9989 to 0.9998 and from 0.9983 to 0.9994 for TH, which showed the applicability of PSK in the adsorption process.…”
Section: Resultsmentioning
confidence: 99%
“…While Ho-McKay’s PSK model was used to fit the data, the correlation coefficients ( R 2 ) of LLB-MB and LLB-MB@Fe 3 O 4 ranged from 0.9987 to 0.9998 and from 0.9964 to 0.9998 for RhB and ranged from 0.9989 to 0.9998 and from 0.9983 to 0.9994 for TH, which showed the applicability of PSK in the adsorption process. In addition, the adsorption processes of LLB-MB and LLB-MB@Fe 3 O 4 for RhB and TH may be chemical reactions, and the adsorption behaviors of chemisorption bonds formed by transfer, exchange, or sharing can control the adsorption rate and affect the adsorption process of the adsorbents [ 28 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In order to elucidate the release mechanism of CBD from the micelles, the release profiles were fitted by linear regression to several kinetic models: order Higuchi and Korsmeyer-Peppas (Figures S6 and S7). Data are present For a more accurate interpretation of the data from the dissolution test, we conducted a non-linear regression analysis [73,74] whereby the drug-relea fitted to the Korsmeyer-Peppas model using DDSolver-a freely available software [75]. The results are summarized in Table S3.…”
Section: In Vitro Drug Release and Cytotoxicity Assaymentioning
confidence: 99%